The Relationship Between Faith and Reason: A Biblical and Philosophical Exploration - Susan, Kemigisha (Advances in Social Sciences Research Journal, 2025)
This PhD thesis explores the complex and multifaceted relationship between faith and reason, examining the intersections and tensions between these two concepts in biblical, philosophical, and contemporary contexts. Through a qualitative research approach, incorporating literature reviews, case studies, and theoretical analysis, this study investigates the ways in which faith and reason inform and shape each other, and the implications of this relationship for critical thinking, problem-solving, and social justice. The study draws on biblical hermeneutics and philosophical analysis, integrating the works of influential thinkers such as Immanuel Kant, Søren Kierkegaard, and C.S. Lewis. The findings highlight the interconnectedness of faith and reason, emphasizing the importance of integrating these concepts in various contexts, including education, ethics, and personal growth. This research contributes to ongoing debates about the nature of faith and reason, and their interrelationship, offering insights into the ways in which these concepts can be integrated and applied in various contexts. The study argues that a nuanced understanding of the relationship between faith and reason is essential for fostering critical thinking, promoting social justice, and addressing the complex challenges of the 21st century.